Goma do cajueiro (Anacardium occidentale): caracterização, microencapsulamento do α-bisabolol e avaliação do efeito cicatrizante em camundongos - Rodrigues Filho, José Marcos Sousa (2020)
Cashew gum - GC (Anacardium occidentale) is a natural polymer used in the preparation of microparticles. Α-bisabolol - BISA is a sesquiterpene widely used in pharmaceutical and cosmetic formulations. However, it is volatile and unstable. This work aimed to chemically characterize a cashew gum and to prepare cashew gum microparticles containing α-bisabolol (CG / BISA). The anti-inflammatory effect CG / BISA was also investigated. The analysis of cashew gum (1H NMR and 13C NMR; GC - FID) revealed a high content of carbohydrates, consisting mainly of galactose (71%). In addition, one GC showed low and low microbiological susceptibility (14% and 0.6). The gum has a diversity of minerals, with calcium found in the highest proportion (1500 mg / kg). The GC / BISA microparticles show a spherical shape (0.7 µm in diameter) and 1.5% α-bisabolol (CLAE-DAD). Thermal analysis (Thermogravimetry and Differential Scanning Calorimetry) showed that a cashew gum was able to primarily protect α-bisabolol up to approximately 200 ° C. pressure in mice. This research developed a new microparticle of CG / BISA, which showed a promising anti-inflammatory activity, with potential for use in the treatment of inflammatory diseases.